Metodološki pristup analizi dalmatinskoga gradskog plemstva - Andreis, Mladen (Acta Histriae, 2008)
Data from Heyer von Rosenfeld's Wappenbuch des Königreichs Dalmatien (Heraldryof the Kingdom of Dalmatia) is often quoted in encyclopedic biographical reference books, such as the Croatian Register of Nobility and the Croatian Biographical Lexicon. However, a thorough analysis of Tragurin nobility revealed that approximately two thirds of the kindred (86 out of 130) that Ronsenfeld's heraldry lists among Tragurin nobility in fact were not actually members. The findings presented in the article were reached through the application of genealogical analysis of a database compiled based on minutes of municipal councils, municipal archives, family archives, municipal registers, and other sources; using appropriate computer applications members of the urban nobility in the period from the 13th century through 1805 were authenticated. Within the examined six centuries, two periods required unique methodological approaches. The main problem when analyzing the medieval period lies in the identification of family membership of individuals frequently recorded only with their personal and their fathers' names (in the 13th and 14th centuries most family names were not formed yet). An additional problem characterizing the period preceding the closure of councils (up to the first half of the 14th century) is the identification of the town councilor. Given the increasing frequency of conferring noble titles since the 16th century onwards and the development of new nobility in the restored communes of Skradin and Nin, archival sources reveal that some individuals would be addressed as nobile or conte while no additional information on what defined their status can be found. Some noblemen permanently lived in specific towns; however, their titles as nobles did not derive from their affiliation with the town council. In addition, noblemen addressed as conte could be granted a national nobility status while also being members of the town councils in the towns where they lived as well as in other towns. Often the noble title would be mentioned only to be polite. Therefore, the origin of noble titles that the sources frequently do not mention needs to be determined. The possible applications of computer-based methods in the analysis of a genealogical database are shown based on the analysis of nuptial matters, which represents a significant parameter of the nobility as an isolated class. Using this method the marriages among nobility members through centuries were analyzed, taking into consideration their class status (nobility, citizenry) and noble origins. In addition, quantitative indicators of endogamy as a measure of closeness of separate isolates were examined.
Keywords: Dalmacija; Dalmatia; genealogija; genealogy; genealoška metoda; mesta; plemstvo; Trogir